Advanced Research in Materials Science - Davaasambuu, Jav; Temuujin, Jadambaa (Diffusion and defect data, Part B, Solid state phenomena,, 2018)
This volume contains peer-reviewed papers presented at the 6th International Conference on Materials Science (ICMS2017, Mongolia, August 18-21, 2017) and focuses on the research of the structure of materials, their properties and characterization techniques as well as their applications in various areas of engineering practice.